Assessment of cortisol as salivary psychological stress marker in relation to temporomandibular disorders among a sample of dental students - Sarmad Qays; Raja Hadi (College of Dentistry/ University of Baghdad, 2015)
Background: University dental students perceived a higher level of stress prior to the final exam associated with raised salivary cortisol levels which could be considered as a useful noninvasive biomarker for measuring acute stress. Using a Helkimo anamnestic and clinical dysfunction scoring for temporomandibular disorders can give a better insight about the association of this marker and temporomandibular joint disorders. The aim of this study was to evaluation level of salivary cortisol in stressor students with temporomandibular disorder and the relation between this marker in relation to temporomandibular disorder severity. This might give a better understanding to the role of psychological stress as an etiological factor for developing temporomandibular joint problems. Materials and methods: A total eighty participants age between 20 to 24 were recruited for this study. The participants were University dental students under graduate students at final examination period who were examined and gave saliva samples in final examination period. Salivary assay kits as cortisol was used to measure those variables and a Helkimo anamnestic and clinical dysfunction scoring for TMD. Results: The group of participants with stress and temporomandibular disorder showed significantly higher levels of salivary cortisol than the control group, the salivary cortisol has statistically significant correlation with Helkimo anamnestic categories (Di-I mild, Di-II moderate and Di-III severe. Salivary cortisol levels show significant but weak association with two categories of clinical dysfunction criteria in Helkimo index system, which are Muscle pain and TMJ pain on palpation. Conclusion: This study demonstrated that University students perceived a high level of stress before the final examination. Salivary cortisol is the stress biomarker that is most often used to measure acute stress. Helkimo anamnestic and clinical dysfunction scoring criteria for still the pioneer for measuring a temporomandibular disorder.